CDNF and MANF in the brain dopamine system and their potential as treatment for Parkinson’s disease - Pakarinen, Emmi; Lindholm, Päivi (Frontiers in Psychiatry, 2023)
Parkinson’s disease (PD) is a progressive neurodegenerative disease characterized by gradual loss of midbrain dopamine neurons leading to impaired motor function. Preclinical studies have indicated cerebral dopamine neurotrophic factor (CDNF) and mesencephalic astrocyte derived neurotrophic factor (MANF) to be potential therapeutic molecules for the treatment of PD. CDNF was proven to be safe and well tolerated when tested in Phase I-II clinical trials in PD patients. Neuroprotective and neurorestorative effects of CDNF and MANF were demonstrated in animal models of PD where they promoted the survival of dopamine neurons and improved motor function. However, biological roles of endogenous CDNF and MANF proteins in the midbrain dopamine system have been less clear. In addition to extracellular trophic activities, CDNF/MANF proteins function intracellularly in the endoplasmic reticulum (ER), where they modulate protein homeostasis and protect cells against ER stress by regulating the unfolded protein response (UPR). Here, our aim is to give an overview about the biology of endogenous CDNF and MANF in the brain dopamine system. We will discuss recent studies on CDNF and MANF knockout animal models, and effects of CDNF and MANF in preclinical models of PD. To elucidate possible roles of CDNF and MANF in human biology, we will review CDNF and MANF tissue expression patterns and regulation of CDNF/MANF levels in human diseases. Finally, we will discuss novel findings related to the molecular mechanism of CDNF and MANF action in ER stress, UPR, and inflammation, all of which are mechanisms potentially involved in the pathophysiology of PD.